2009
DOI: 10.3746/jkfn.2009.38.2.252
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Evaluation of Foods and Kitchen Environments in Childcare Center and Kindergarten Foodservice Operations

Abstract: Whereas the numbers of childcare centers and kindergartens are increasing rapidly, systematic management to control the food safety of foodservice operation is not yet well established. Samples from 12 centers in Seoul and Gyeonggi Province were collected to assess the microbiological quality of 32 raw materials, 24 cooked foods, 76 food-contact surfaces (knives, cutting boards, dish towels and gloves), 17 employees' hands and 12 air-borne bacteria. The microbiological analyses were performed for aerobic plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…For example, approximately 5.6 log CFU of aerobic mesophiles per g was isolated from salad lettuce that had not yet been washed (13). In another study (19), more than 6 log CFU of aerobic bacteria per g was detected in seasoned Chinese cabbage. Seol et al (19) monitored the microbial quality of seasoned Chinese cabbage during preparation and detected approximately 5 and 6 log CFU of aerobic mesophiles per g from samples before and after preparation, respectively.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, approximately 5.6 log CFU of aerobic mesophiles per g was isolated from salad lettuce that had not yet been washed (13). In another study (19), more than 6 log CFU of aerobic bacteria per g was detected in seasoned Chinese cabbage. Seol et al (19) monitored the microbial quality of seasoned Chinese cabbage during preparation and detected approximately 5 and 6 log CFU of aerobic mesophiles per g from samples before and after preparation, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…Three or more log CFU of coliforms per g was also detected from one heated/ nonheated sample and six dessert samples. Another study (19) reported that approximately 2.6 log CFU of coliform per g was isolated from seasoned Chinese cabbage served in schools. However, we found .3 log CFU of coliforms per g from all samples of seasoned Chinese cabbage in school A.…”
Section: Resultsmentioning
confidence: 99%